Pathways to tertiary education in the English-speaking Caribbean - Best, Gladstone (UWI. Tertiary Level Institution Unit BridgetownBB, 2003)
Establishes and documents the different pathways which are being used in a range of tertiary education settings within the Caribbean and specifically in the 15 countries which contribute to the funding of the regional university.